2012
DOI: 10.1590/s0100-40422012000300025
|View full text |Cite
|
Sign up to set email alerts
|

Citotoxicidade e genotoxicidade de nanotubos de carbon

Abstract: Recebido em 2/5/11; aceito em 6/9/11; publicado na web em 8/11/11 CYTOTOXICITY AND GENOTOXICITY OF CARBON NANOTUBES. There are many controversies regarding the cyto-and genotoxicity of carbon nanotubes (CNTs). In this work, we discuss that many of the incongruous arguments are probably associated with the poor physical-chemical characterization of the CNT samples used in many publications. This manuscript presents examples of carbon nanostructures observed under high resolution electron microscopy that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…Although cell viability assays performed by a few researchers have detected that SWCNT samples containing residual iron have a high cytotoxic potential (Franchi et al, 2011), the MWCNT samples used in the present study catalyzed with C, O and Fe demonstrated no cytotoxicity according to the test applied. This finding may be associated with the high levels of purity of the nanotubes used in our study: only 1.5% from iron oxide and the other 98.5% from carbon.…”
Section: Genotype and Compoundsmentioning
confidence: 56%
See 2 more Smart Citations
“…Although cell viability assays performed by a few researchers have detected that SWCNT samples containing residual iron have a high cytotoxic potential (Franchi et al, 2011), the MWCNT samples used in the present study catalyzed with C, O and Fe demonstrated no cytotoxicity according to the test applied. This finding may be associated with the high levels of purity of the nanotubes used in our study: only 1.5% from iron oxide and the other 98.5% from carbon.…”
Section: Genotype and Compoundsmentioning
confidence: 56%
“…Results obtained in another study using single walled carbon nanotubes and graphite nanofibers (3.8-380 lg/mL), evaluated by the comet test, also demonstrated a correlation between genotoxicity and the activity of metal catalysts present in the material (Lindberg et al, 2009). The toxicity and genotoxicity mechanisms of the CNTs have not yet been fully clarified and there is a need for more research in this area (Franchi et al, 2011), but evidence suggests points of similarity between CNTs and asbestos fibers, due to the generation of reactive oxygen species and oxidative stress (Sanchez et al, 2009). Although cell viability assays performed by a few researchers have detected that SWCNT samples containing residual iron have a high cytotoxic potential (Franchi et al, 2011), the MWCNT samples used in the present study catalyzed with C, O and Fe demonstrated no cytotoxicity according to the test applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Despite some disadvantages such as low solubility and that they will not be easily discharged from the body, there has been increasing interest during the past two decades for using CNTs in drug delivery. [33][34][35][36] Using CNTs for drug delivery causes reduction in the dosage of the intended drug and consequently the reduction of its side effects. 37,38 Covalent and noncovalent (hydrogen bonds and van der Waals interactions) functionalizations perform a principle role in the drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…The mitotic index (MI) is a parameter used to assess the growth of cell populations in vitro and their regeneration capacity, and also is used to the identification of several mitotic abnormalities associated with the age of the cultures (Franchi et al 2012). This parameter can also be used as an indicator of adequate proliferation of cells, mainly applied in mutagenicity and toxicity studies (Gadano et al 2002;Rogero et al 2003).…”
Section: Introductionmentioning
confidence: 99%